2015
DOI: 10.5829/idosi.ijee.2015.06.01.09
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Trace Elements Toxicity Through Contaminated Edible Plants from Polluted Irrigation Canal at Giza Governorate, Egypt

Abstract: To assess the leakage of sanitation service in urban areas on the contamination of water streams and soil besides, a risk assessment study was conducted through the intake of edible plants from polluted irrigated suburban area of El-Zomor area, Egypt. The results revealed that concentrations of trace elements were several folds higher in the studied site compared to the background level in the earth crust indicating that the soil of the studied area is contaminated with heavy metals. Therefore, contamination f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(20 reference statements)
1
0
0
Order By: Relevance
“…This is mainly due to the clay texture of the sediment which can accumulate excessive amounts of elements on the surface. These results are in a good agreement with (El-Kholy et al, 2015;Sherif et al, 2015) which reported that the values of trace elements are considerably below the permissible limits. (Ayers and Westcot, 1985).…”
Section: Micro-nutrients and Heavy Metals In Irrigation Watersupporting
confidence: 91%
“…This is mainly due to the clay texture of the sediment which can accumulate excessive amounts of elements on the surface. These results are in a good agreement with (El-Kholy et al, 2015;Sherif et al, 2015) which reported that the values of trace elements are considerably below the permissible limits. (Ayers and Westcot, 1985).…”
Section: Micro-nutrients and Heavy Metals In Irrigation Watersupporting
confidence: 91%